Materiais multifuncionais envolvendo ZrO2 puro ou em sistemas core@shell para remediação ambiental e produção de biodiesel - Neris, Alex de Meireles (2019)
The growth of environmental problems has triggered the pursuit of clean and renewable energetic solutions as well as the development of methodologies for waste treatment. This work aims to apply pure and core@shell systems based ZrO2 properties on biodiesel synthesis, adsorption and photodegradation of organic pollutants, the materials were employed as heterogeneous photocatalyst for transesterification reaction, as photocatalyst for organic dyes degradation and also as adsorptive material for waste treatment and pigments formation. Modified Pechini method was employed for zirconia and core@shell systems synthesis. Samples obtained were submitted to structural, electronic and catalytic properties characterization. Tetragonal and monoclinic phases of ZrO2 were obtained at 600ºC and 1000ºC, respectively, and were evaluated as catalysts for transesterification reactions, in a Parr reactor employing ethylic route with soybean oil, optimizing time and temperature reaction. Zirconia is not catalytic effective, but sulfated samples reached 95% of soybean conversion into ethylic esters. On the other hand, aiming to combine magnetic and photocatalytic properties, core@shell systems with (CoMn)Fe2O4 nanoparticles as core and different ratios of ZrO2 and TiO2 as shells were synthesized. Besides employing an unusual methodology for obtainment of core@shell systems, the novelty of this work is also the use of an intermediate shell of ZrO2 in order to reduce electronic interaction between (CoMn)Fe2O4 and TiO2. Decolorization reaction, through photocatalysis or adsorption tests were perfomed under stirring in a quartz reactor with low power UVC lamps (λ = 254 nm, 9 W), and photocatalytic or adsorption efficiency were evaluated for different reaction times and different kinds of dyes, namely remazol golden yellow (RNL) and methylene blue (MB). Photocatalytic products were analysed with UV-Vis spectroscopy, used to monitor dye solution concentration after different times of irradiation. ZrO2 synthesized and calcined at 600°C, with majority of tetragonal phase, reached the highest adsorptive ability with decolorization of MB solution (initial concentration 10 mg.L-1 ) after 16 h of adsorption test, reaching 15 mg.g-1 of adsorptive ability. The formation of a stable pigment was identified, with the adsorption of the dye to the catalyst surface Photocatalytic activity of core@shell systems were related to TiO2 content, with the best results obtained for samples containing an intermediate shell of ZrO2, reaching 96% decolorization of MB solution with 85% TiO2 sample.